Application of interactive charts in the evaluation of socio-economic development of regions; the case of Poland - Karol Król; Barbara Prus (Acta Scientiarum Polonorum. Formatio Circumiectus)
The paper presents multidimensional interactive data charts as a tool to support presentation and characteristics of spatial phenomena. The phenomenon of socio-economic development of provinces has been analysed, as defined in multidimensional space of variables. Classification of objects was performed using the method of zero unitarization. Statistical data have been obtained from public sources, compiled in the form of a matrix, and then subjected to normalization in order to bring the tested objects to direct mutual comparability. The studies allowed us to observe great diversity in socio-economic development of regions. The analysis of line distribution of development meta-variables (indices) revealed that their biggest values concerned the group of social factors, and the smallest concerned the natural (environmental) ones. In the conclusion, it was pointed out that interactive visualizations of data complement the tabular form of their presentation, and they facilitate an analysis of phenomena in spatial terms, while showing their internal structure and also the correlations between individual objects.